Importance of regional climates for plant species distribution patterns in moist Afromontane forest. (27th September 2012) - Schmitt, Christine B.; Senbeta, Feyera; Woldemariam, Tadesse; Rudner, Michael; Denich, Manfred; Fridley, Jason
Abstract Questions How are plant species distribution patterns in tropical montane forest linked to altitude, regional climate and geographic location? Which climatic variables are most important in explaining variations in floristic diversity? What are potential effects of climate change on species diversity? Location Ethiopia. Methods Vegetation surveys were conducted in 180 study plots distributed across five moist montane forest areas in southwest and southeast Ethiopia (1000–2300 m a.s.l.). Temperature and precipitation data, as well as bioclimatic variables, were derived for each study plot from the WorldClim global climate data set. Species and climate data were analysed with direct and indirect ordination techniques and multivariate regression trees (MRT). Results Each of the sampled forest areas showed a distinct species composition and was governed by a particular regional temperature and precipitation pattern related to the topographic variability of the Ethiopian highlands. Hence, a general altitudinal cut‐off level for different forest types applicable in all five moist montane forest areas could not be identified. The most important bioclimatic variable in determining species distribution patterns was the amount of precipitation after the dry season (i.e. precipitation in the warmest quarter), followed by minimum temperature in the coldest month. At a lower hierarchical level, temperature and precipitation seasonality were also identified as significant discriminating variables. Generally, in areas with high precipitation during the warmest quarter (≥288 mm) and low minimum temperature in the coldest month (<10.9 °C), the number of Afromontane species was highest and that of Guineo–Congolian species lowest. Conclusions The altitudinal effect on species diversity in the Ethiopian moist montane forests is strongly modified by regional differences in precipitation and temperature regime. The predicted increase in temperature for the Ethiopian highlands due to climate change is likely to affect the distribution of the endemic Afromontane species. Furthermore, the study highlights the need for systematic on‐the‐ground measurements of climate variables in tropical montane areas in order to understand the current climate regime and as a basis for modelling future changes.